Eccentric cycling emphasising a low cardiopulmonary demand increases leg strength equivalent to workload matched concentric cycling in middle age sedentary males. Issue 12 (December 2018) - Lewis, Michael C.; Peoples, Gregory E.; Groeller, Herbert; Brown, Marc A.
Abstract: Objectives: This study determined if eccentric endurance cycling, eliciting a low cardiovascular demand, could stimulate muscle strength adaptations in sedentary middle-aged males. Design: Twenty-four middle-aged sedentary males were allocated to concentric (CON ) or matched workload eccentric (ECC ) cycling (60% peak concentric workload) according to their maximal voluntary isometric quadriceps strength. Methods: Seventeen participants [42.7 ± 8.3 years, BMI 28.6 ± 5.2, peak oxygen consumption [30.5 ± 5.8 mL kg −1  min −1 ] completed 8 weeks (2 sessions per week) ofCON (n = 8) orECC (n = 9) cycle training. Incline leg press (6RM), maximal voluntary isometric contraction (MVIC) torque of the quadriceps and peak oxygen consumption were measured at baseline and 8 weeks. Results: Eccentric cycle training resulted in low cardiovascular demand (CON 154 ± 2;ECC 95 ± 3 b min −1 P <  0.05) and ratings of perceived exertion (CON 14.9 ± 0.3;ECC 9.5 ± 0.3/20 P <  0.05). Peak oxygen consumption improved within theCON group (Baseline 27.4 ± 2.1; 8 weeks: 30.0 ± 1.7 mL kg −1  min −1 P <  0.05) and not within theECC group (Baseline 33.2 ± 1.5; 8 weeks 33.3 ± 1.6 mL kg −1  min −1 ) following training. 6RM (CON 176 ± 20;ECC 192 ± 11 kg) and MVIC (CON 199 ± 25;ECC 199 ± 25 Nm) strength were equivalent at baseline ( P >  0.05). Both groups significantly increased 6RM (CON 13.0 ± 3.0;ECC 10.7 ± 3.2%) and MVIC (CON 12.9 ± 4.3;ECC 18.8 ± 3.0%) relative to their own baseline ( P  < 0.05). Therefore, improved leg strength was equivalent betweenCON andECC groups despite the varied training ( P  > 0.05). Conclusions: In sedentary middle age males, eccentric endurance cycling with a low cardiovascular demand, increased both quadriceps isometric and 6RM strength comparable to a matched workload concentric cycling program.